1996
DOI: 10.1039/cc9960000589
|View full text |Cite
|
Sign up to set email alerts
|

Cooperativity in ligand binding expressed at a model cell membrane by the vancomycin group antibiotics

Abstract: Dimerisation or the use of a membrane anchor enhances the binding of the glycopeptide antibiotics at the surface of a model cell membrane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
50
0
3

Year Published

1999
1999
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(54 citation statements)
references
References 9 publications
1
50
0
3
Order By: Relevance
“…[71] Moreover, the chemical shift of w 2 (which was shown earlier to occur at lower field the more strongly the ligand was bound to it) in the latter assembly occurs further downfield (d 11.65) than for the former association (d 11.43). [71] Similar results were achieved for teicoplanin binding to the peptides Ac 2 -KdAdA and N-a-decanoyl-N-e-acetyl-lysyl-d-alanyl-d-alanine (DecKdAdA) in the presence of micelles. As for ristocetin A binding to Dec-dAdA and Ac-dAdA, the binding constant of teicoplanin to Dec-KdAdA was greater than that to Ac 2 -KdAdA and w 2 was shifted further downfield for the binding of Dec-KdAdA than for the binding of Ac 2 -KdAdA.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…[71] Moreover, the chemical shift of w 2 (which was shown earlier to occur at lower field the more strongly the ligand was bound to it) in the latter assembly occurs further downfield (d 11.65) than for the former association (d 11.43). [71] Similar results were achieved for teicoplanin binding to the peptides Ac 2 -KdAdA and N-a-decanoyl-N-e-acetyl-lysyl-d-alanyl-d-alanine (DecKdAdA) in the presence of micelles. As for ristocetin A binding to Dec-dAdA and Ac-dAdA, the binding constant of teicoplanin to Dec-KdAdA was greater than that to Ac 2 -KdAdA and w 2 was shifted further downfield for the binding of Dec-KdAdA than for the binding of Ac 2 -KdAdA.…”
mentioning
confidence: 94%
“…As for ristocetin A binding to Dec-dAdA and Ac-dAdA, the binding constant of teicoplanin to Dec-KdAdA was greater than that to Ac 2 -KdAdA and w 2 was shifted further downfield for the binding of Dec-KdAdA than for the binding of Ac 2 -KdAdA. [71] Thus, in the formation of templated assemblies, not only is there the advantage of a relatively small adverse entropy (the binding being effectively intramolecular), but the motional restriction associated with binding at a template (the micelle surface) is also associated with stronger bonding of the peptide carboxylate into its receptor pocket.…”
mentioning
confidence: 95%
“…In the presence of doc-KAA, the binding of teicoplanin was also enhanced; attributed to cooperative binding of precursors analogues binding and membrane anchoring [10]. This explains why teicoplanin at lower concentrations also showed significant responses, whereas significant binding for vancomycin is only observed when concentrations are sufficient to lead to a dimer population at the membrane surface [33][34][35]37].…”
Section: Discussionmentioning
confidence: 67%
“…Teicoplanin binds to membranes in the absence of doc-KAA, due to the lipophilic C 11 acyl chain, which can serve as a membrane anchor to localize the antibiotic in the membrane [34,35]. The fatty acid chain enhances the lipophilicity of the compound partition coefficient (log P) of teicoplanin (À2.26), compared with vancomycin (À4.41) [36].…”
Section: Discussionmentioning
confidence: 98%
“…1c and d) by an alkylation of a chlorobenzylphenyl side chain (green) at the 4-epi-vancomsamine on the fourth amino acid and an additional 4-epi-vancomsamine (purple) at the sixth amino acid of the aglycon. Since oritavancin readily forms dimers in solution and binds to membrane vesicles (8), drug dimerization and membrane anchoring mediated by the hydrophobic side chain of oritavancin are thought to increase its binding to the D-Ala-D-Lac-terminated PG stem structure to overcome the vancomycin resistance in VRE (9). However, in situ characterizations of oritavancin (10) and oritavancin-like glycopeptide (4,11,12) binding sites in intact whole cells of S. aureus by solid-state nuclear magnetic resonance (NMR) have shown that lipoglycopeptides do not bind to the cell wall as dimers or partition to the bacterial membrane.…”
mentioning
confidence: 99%